Seasonal Abundance of Culex tarsalis and Culex pipiens Complex Mosquitoes (Diptera: Culicidae) in California - BARKER, CHRISTOPHER M. (2010)
Large-scale patterns in the seasonal abundance profiles of the arboviral mosquito vectors Culex tarsalis Coquillett and the species of the Culex pipiens complex were described based on a decade of counts from 868 New Jersey light traps located throughout the urban and agricultural areas of California. Mean seasonal abundance profiles varied markedly among hydrologic regions. For all species, abundance increased earlier and declined later in drier, warmer southern regions, but variation could not be explained fully by latitude. The observed patterns may be driven by temperature, availability of larval habitats, and for the Cx. pipiens complex, the taxonomic composition of local populations.